Evaluation of Thermal Conditions in the GKB 2 Unimus Hall Using Temperature and Relative Humidity Parameters - Clarisa Isnaini Aulia Dewi; Mohhamad Kusyanto (TERRACE: JOURNAL OF ARCHITECTURE & URBAN STUDIES, 2026)
This study aims to evaluate the thermal conditions in the hall on the 8th floor of GKB 2 Building, Muhammadiyah University of Semarang (Unimus) using temperature and relative humidity as the main indicators. The background of this study is the importance of thermal comfort in higher education spaces that directly impact the productivity and health of space users. Data collection was carried out periodically every hour from 06.00 to 18.00 at five observation points spread throughout the room. The measurement method used a digital hygrometer and supported by data analysis using Microsoft Excel to produce a graph of temperature and humidity fluctuations. The results show a general pattern that occurs in closed spaces in tropical climates, namely the temperature increases until midday and decreases in the afternoon, while relative humidity shows the opposite trend. This study provides an overview of the importance of ventilation management and space design strategies that are able to maintain thermal comfort throughout the day.